Assessment of the Impact of External Borrowing on the Economic Growth of the Developing Countries - Nigerian Experience (Asian Business Research, 2018)
This paper examines the impact of foreign borrowing on the economic growth of the developing nations using Nigeria as a case study. Time series data from 1985 and 2015 were sourced from Central Bank of Nigeria Statistical Bulletin and other related journals. Data sourced were analyzed using Durbin Watson auto correlation to test for the reliability of the data and diagnostic tests such as unit root test (Augmented Dickey Fuller) and Johansen co-integration to test for the non-stationary of the data and long run relationship between the dependent and independent variables. OLS multiple regressions were used as estimation technique to test for the relationship between the explanatory variables and economic growth. The study revealed that there is significant relationship between economic growth, exports, capital investment and debt service payment but external debt and exchange rate have a significant inverse relationship with economic growth. The study concludes that, capital investment, exports and debt service payment have impact on economic growth but external debt and exchange rate do not. Therefore, the study recommends that, purpose of borrowing should be considered important while channeling the borrowed funds and efficient utilization of the funds to solve the purpose by which it was acquired will go a long way to impact growth on the economy of the country.